2017
DOI: 10.1016/j.biocel.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased deposition of glycosaminoglycans and altered structure of heparan sulfate in idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by aberrant deposition of extracellular matrix (ECM) constituents, including glycosaminoglycans (GAGs), that may play a role in remodelling processes by influencing critical mediators such as growth factors. We hypothesize that GAGs may be altered in IPF and that this contribute to create a pro-fibrotic environment. The aim of this study was therefore to examine the fine structure of heparan sulfate (HS), chondroitin/dermatan sulfate (CS/DS) and hyaluronan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…HSPGs are upregulated in many human fibrotic conditions, including human idiopathic lung fibrosis (Jiang et al, 2010; Westergren-Thorsson et al, 2017), Duchenne’s Muscular Dystrophy (Alvarez et al, 2002), liver disease (Roskams et al, 1996) and kidney fibrosis (Ebefors et al, 2011). Additionally, heparanase, the enzyme that metabolizes the carbohydrate chains on these proteoglycans, is also upregulated in fibrotic pathologies (Lv et al, 2016).…”
Section: Activators Of the Smad-2/3 Axis And Fibrosismentioning
confidence: 99%
“…HSPGs are upregulated in many human fibrotic conditions, including human idiopathic lung fibrosis (Jiang et al, 2010; Westergren-Thorsson et al, 2017), Duchenne’s Muscular Dystrophy (Alvarez et al, 2002), liver disease (Roskams et al, 1996) and kidney fibrosis (Ebefors et al, 2011). Additionally, heparanase, the enzyme that metabolizes the carbohydrate chains on these proteoglycans, is also upregulated in fibrotic pathologies (Lv et al, 2016).…”
Section: Activators Of the Smad-2/3 Axis And Fibrosismentioning
confidence: 99%
“…Interestingly, the mature osteoarthritis cartilage contains CS with an especially high level of 6‐ O ‐sulfation , which could functionally compensate for the loss of a GAG that has such a composition in the disease‐affected tissue areas. An increased content of 6‐ O ‐sulfated CS disaccharides and an elevated deposition of CS/DS have also been shown to characterize the tissue remodeling that is associated with fibrosis . However, in contrast to the metabolic changes of CS/DS in the tumor microenvironment, in the fibrosis‐affected tissues there is also a proportional elevation of the 4‐ O ‐sulfation in CS/DS so that the normal ratio between the 6‐ O ‐ and 4‐ O ‐sulfated disaccharides is preserved in these GAGs .…”
Section: Insights Into the Biological Relevance Of 6‐o‐sulfation Of Cmentioning
confidence: 99%
“…An increased content of 6‐ O ‐sulfated CS disaccharides and an elevated deposition of CS/DS have also been shown to characterize the tissue remodeling that is associated with fibrosis . However, in contrast to the metabolic changes of CS/DS in the tumor microenvironment, in the fibrosis‐affected tissues there is also a proportional elevation of the 4‐ O ‐sulfation in CS/DS so that the normal ratio between the 6‐ O ‐ and 4‐ O ‐sulfated disaccharides is preserved in these GAGs . Interestingly, a recent study using an animal model of lung fibrosis showed that substantial alterations in the CS/DS metabolism begin in the inflammatory phase of this process and that they are regulated by TGFβ1, which also plays a crucial role in the tumor progression .…”
Section: Insights Into the Biological Relevance Of 6‐o‐sulfation Of Cmentioning
confidence: 99%
“…[8][9][10] In healthy adult human lungs, the total amounts of chondroitin sulfate/dermatan sulfate (CS/DS), HA, and HS were found to be equal. 11 Not as much is known about the importance of CS, DS, or keratan sulfate (KS) PGs in lung morphogenesis. There is evidence that the amount of CS progressively diminishes during development especially in the lung parenchyma.…”
Section: Pgs In Developing and Healthy Lungsmentioning
confidence: 99%